Self‐reported prevalence, description and management of pain in adults with haemophilia: methods, demographics and results from the Pain, Functional Impairment, and Quality of life (P‐FiQ) study. Issue 4 (16th April 2017) - Witkop, M.; Neff, A.; Buckner, T. W.; Wang, M.; Batt, K.; Kessler, C. M.; Quon, D.; Boggio, L.; Recht, M.; Baumann, K.; Gut, R. Z.; Cooper, D. L.; et al.
Abstract : Introduction: Haemophilia is characterized by frequent haemarthrosis, leading to acute/chronic joint pain. Aim: To assess self‐reported prevalence, description and management of pain in adult males with mild‐to‐severe haemophilia and history of joint pain/bleeding. Methods: Participants completed a pain survey and five patient‐reported outcome instruments assessing pain, functional impairment and health‐related quality of life (HRQoL). Results: Of 381 participants enrolled, median age was 34 years; 77% had haemophilia A, 71% had severe disease and 65% were overweight/obese. Many (56%) were not receiving routine infusions; 30% never received routine infusions. During the prior 6 months, 20% experienced acute pain, 34% chronic pain and 32% both acute/chronic pain. Subjects with both acute/chronic pain (vs. none, acute or chronic) were more likely to be depressed (30% vs. 0–15%), obese (35% vs. 20–29%) and have lower HRQoL (mean EQ‐5D visual analog scale, 69 vs. 83–86) and function (median overall Hemophilia Activities List, 60 vs. 88–99). Most common analgesics used for acute/chronic pain during the prior 6 months were acetaminophen (62%/55%) and non‐steroidal anti‐inflammatory drugs (34%/49%); most common non‐pharmacologic strategies were ice (65%/33%) and rest (51%/33%). Hydrocodone‐acetaminophen was the most common opioid for both acute/chronic pain (30%); other long‐acting opioids were infrequently used specifically for chronic but not acute pain (morphine, 7%; methadone, 6%; fentanyl patch, 2%). Conclusion: Patients with chronic pain, particularly those with both acute/chronic pain, frequently experience psychological issues, functional disability and reduced HRQoL. Treatment strategies for acute pain (e.g. routine infusions to prevent bleeding) and for chronic pain (e.g. long‐acting opioids) may be underused.